Juvenile Delinquency and Medico-Legal Perspective for Promoting Children’s Health - Dokudan, Erenç Yasemin; Uzunyayla, Zuhal; Bilgi, Sefer; Ünüvar, Ümit (Eastern Journal of Medical Sciences, 2019)
Background: Risk factors such as biological, psychological, sociological, cultural, economic and environmental factors have been defined for juvenile delinquency. Identification of these risk factors is necessary in terms of creating a management plan of the cases, and for planning protective and preventive activities. Objective: To discuss the potential of forensic evaluation in improving the health of the children, and practical difficulties and to evaluate the risk factors and protection needs of children involved in crime. Method: Data of the children between the age group of 12-18 years, who attended the Forensic Medicine Policlinic during the time period of 08th October 2015 – 31st January 2016, were taken for evaluation, retrospectively. Age, gender, socio-demographic data and reasons for evaluation were investigated. Results: Out of the 89 cases included in the study, 12 were girls (13%), 77 were boys (87%), and the mean age was 15.14. Custody examination was the most common reason of the application with 76 cases (85%). In the studied group, 60 children had the habit of smoking, and 24 were using alcohol/substance, while 36 of them were working. The mean period of education was 7.18 years; in this study, 3 children were living on the streets, 4 were staying at a children’s dormitory (society for protection of children), 5 were living with their friends. New or recent blunt traumatic lesions were detected on the examination of 20 children. Conclusion: In our retrospective study, risk factors of juvenile delinquency were evaluated regarding gender, educational status, family status, working status, smoking and use of alcohol/substance, and these were found to be compatible to the literature. There is a need for future studies where wide risk factors of juvenile delinquency can be evaluated.